2015
DOI: 10.1111/bph.13383
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to inhibit bone resorption: exosite inhibitors against cathepsin K

Abstract: BACKGROUND AND PURPOSECathepsin K (CatK) is a major drug target for the treatment of osteoporosis. Potent active site-directed inhibitors have been developed and showed variable success in clinical trials. These inhibitors block the entire activity of CatK and thus may interfere with other pathways. The present study investigates the antiresorptive effect of an exosite inhibitor that selectively inhibits only the therapeutically relevant collagenase activity of CatK. EXPERIMENTAL APPROACHHuman osteoclasts and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 43 publications
4
62
1
Order By: Relevance
“…OC are multinucleated myeloid cells, specialized to remove mineralized bone matrix through the production of lysosomal enzymes, such as tartrate-resistant acid phosphatase (TRAP) and catepsin k, against which a selective inhibitor (odanacatib) has been recently synthesized to be employed in osteoporotic patients [12]. They derive from a bone marrow precursor which gives rise also to professional antigen presenting cells (APC), i.e.…”
Section: Cellular and Molecular Mechanisms Of Bone Remodelingmentioning
confidence: 99%
See 1 more Smart Citation
“…OC are multinucleated myeloid cells, specialized to remove mineralized bone matrix through the production of lysosomal enzymes, such as tartrate-resistant acid phosphatase (TRAP) and catepsin k, against which a selective inhibitor (odanacatib) has been recently synthesized to be employed in osteoporotic patients [12]. They derive from a bone marrow precursor which gives rise also to professional antigen presenting cells (APC), i.e.…”
Section: Cellular and Molecular Mechanisms Of Bone Remodelingmentioning
confidence: 99%
“…Bisphosphonates, drugs used for some time in the therapy of osteoporosis, are potent inhibitors of OC activity both in the primitive and secondary osteoporosis, such as that associated with autoimmune diseases [61,62]. A decreased BMD in the spine and hip and higher prevalence of osteoporosis have been described in RA patients [63]. In early untreated RA, BMD is related to longer symptom duration, the presence of rheumatoid factor (RF) and cyclic citrulinated peptide antibodies (anti-CCP), disease activity score, and the presence and progression of joint damage [1, 19].…”
Section: Osteoporosis and Inflammation: The Lesson Of Rheumatoid Arthmentioning
confidence: 99%
“…Cortical bone slices (Immunodiagnostic Systems, East Boldon, UK) were purchased for in vitro assessment of osteoclastic bone resorption using pit formation assay as per the procedure described with slight modifications . Bone chips were sterilized under ultraviolet for at least 2 h and then washed with media before placing in 96‐well plates.…”
Section: Methodsmentioning
confidence: 99%
“…We have recently demonstrated that an exosite inhibitor of CatK is capable of inhibiting bone resorption in an osteoclast assay indistinguishable from and with only a slightly lesser potency to that of odanacatib. [170] This compound specifically blocks the collagenase activity of CatK by binding in an exosite remote from the active site without interfering with the degradation of cytokines such as TGF-ß1. Here it is of interest that a previously identified pycnodysostosis-causing point mutation (Y283C) is located in the putative exosite.…”
Section: Expert Opinionmentioning
confidence: 99%